Antibacterial potential and genetic profile of Enterococcus faecium strains isolated from human normal flora. (July 2016) - Karimaei, Samira; Sadeghi, Javad; Asadian, Mahla; Esghaei, Maryam; Pourshafie, Mohammad Reza; Talebi, Malihe
Abstract: Enterococci have a widespread attendance in the circumference and belongs to the enteric commensal microbiota. Most of them produce the antimicrobial compounds and have an inhibition effect on pathogenic microorganisms. The objective of this study was to characterize the enterococcal strains isolated from human normal flora and assess their antibacterial activity. Enterococcal isolates were obtained from the feces of eighteen healthy humans. All enterococcal species were identified by biochemical and species-specific polymerase chain reaction (PCR). These isolates were investigated further to examine their ability to inhibit growth of Salmonella typhi, Shigella flexneri and Escherichia coli by well diffusion assay. Furthermore, antibiotic susceptibility test was performed and genetic relatedness of all isolates was evaluated by Pulse Field Gel Electrophoresis (PFGE). In all, 432 isolates were obtained from fecal samples. All of the isolates identified as Enterococcus faecium by biochemical and molecular (PCR) methods. Using repetitive element palindromic (REP)-PCR method 54 patterns have been obtained and were selected for further evaluation. The results indicated that 66%, 38% and 24% of our isolates had antimicrobial effect against S . typhi, S flexneri and enteroaggregative Escherichia coli (EAEC), respectively. On the other hand, there was no significant inhibition effect against enteropathogenic E. coli (EPEC) and enterotoxigenic E . coli (ETEC). All isolates were sensitive to vancomycin, teicoplanin, linezolid, ampicillin, chloramphenicol and gentamicin. On the other hand, the resistance rates for erythromycin, tetracycline and ciprofloxacin were 20%, 22%, and 1.8% respectively. In addition, the analysis of PFGE showed forty patterns with eight (40.7%) common types (CT) and thirty two (59.2%) single types (ST). Among eight common types, only one common type (CT5) had similar antimicrobial effect. These results suggested that enterococcal isolates obtained from human normal flora have potential antibacterial effect against S . typhi, S . flexneri and E. coli . Highlights: Antibacterial potential of Enterococcal strains isolated from Feces of Human were surveyed. Enterococcus faecium is indigenous bacteria in Iran. Enterococcus faecium isolates have antibacterial effect against Salmonella typhi, Shigella flexneri and Escherichia coli .